(untitled) (Sains Humanika, 2021)
The purpose of this paper is to explore the antecedents of knowledge-sharing behavior among lecturers. This paper integrates the antecedents of knowledge-sharing behavior among lecturers into an integrated theoretical framework. The proposed framework aims to add to the understanding of specific processes to enhance lecturers’ knowledge-sharing behavior intention. This paper is developed based on a literature review. A range of relevant literature was explored, and a theoretical framework is proposed and discussed. The proposed theoretical framework is original; therefore it will contribute to the enrichment of the literature.